The Effect of Real Wages and Economic Growth on Labor Absorption in the Review of Maqashid Syariah in Tanjungbalai City - Nindya Azzahra; Isnaini Harahap; Muhammad Ikhsan Harahap (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to analyze the influence of Real Wages and Economic Growth on employment absorption within the framework of Maqashid Sharia in Tanjungbalai City from 2014 to 2021. It employs secondary data obtained from the Central Bureau of Statistics of Tanjungbalai City, the North Sumatra Provincial Manpower Office, internet media sources, and other literature. The research methodology involves Multiple Linear Regression Analysis. The results indicate that the test results for variable X1 show a significant influence, while those for variable X2 do not. Overall, variables X1 and X2 collectively account for 74.4% of the total influence, with the remaining 25.6% attributed to other variables beyond the model.